2015
DOI: 10.1016/j.jnc.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the terrestrial mammal communities in forests of Central Panama, using camera-trap surveys

Abstract: a b s t r a c tThe Isthmus of Panama, part of the planet's third largest megadiversity hotspot, and connecting the faunas of North and South America, has lost more than half of its forest due to agriculture and economic development. It is unknown to what degree the remaining forest, which is fragmented and subject to poaching, still supports the wildlife diversity found in intact forests. Here, we use camera-trap surveys to assess whether forests in Central Panama, the narrowest and most disturbed portion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 32 publications
(34 reference statements)
1
33
0
Order By: Relevance
“…At the fishbone human settlements IA Bom Jesus and IA Entre Rios, due to the fact that Tayassu pecari has been extirpated, dominance was lower than in PA Maracá (and diversity higher), but was higher still than PA Uatumã (and diversity lower). In these impacted areas the medium-sized Dasyprocta leporina had the highest dominance, possibly replacing Tayassu pecari, as seems also to be the case in Meyer et al (2015) where agoutis, (Dasyprocta leporina) were the most abundant, causing a decline in evenness and dominance.…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 72%
See 4 more Smart Citations
“…At the fishbone human settlements IA Bom Jesus and IA Entre Rios, due to the fact that Tayassu pecari has been extirpated, dominance was lower than in PA Maracá (and diversity higher), but was higher still than PA Uatumã (and diversity lower). In these impacted areas the medium-sized Dasyprocta leporina had the highest dominance, possibly replacing Tayassu pecari, as seems also to be the case in Meyer et al (2015) where agoutis, (Dasyprocta leporina) were the most abundant, causing a decline in evenness and dominance.…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 72%
“…In our previous studies (Mendes Pontes 2004, Mendes Pontes et al 2007, Mendes Pontes et al 2012, Melo et al 2015, we showed that in the highly heterogeneous vegetation mosaics of the northernmost Guyana shield the structure of the terrestrial mammalian assemblages was shaped by forest type and heterogeneity, which, in turn, is directly connected with resource availability. Species richness and diversity may vary between protected and impacted areas, with the latter in most studies presenting a lower number of species due to hunting (Lopes and Ferrari 2000, Peres and Nascimento 2006, Michalski and Peres 2007, Sampaio et al 2010, Ahumada et al 2011, Melo et al 2015, Meyer et al 2015. Accordingly, the richest area was PA Uatumã, located south of the Guyana shield, closest to central Amazonia, the natural vegetation cover for which is dense ombrophilous forests, followed by IA Entre Rios, which is located in the transition between the dense ombrophilous terra firme forests of the south of the Guyana shield, and the seasonally-dry forest mosaics of central Guyana shield, and the poorest areas were PA Maracá and IA Bom Jesus, in the northernmost Guyana shield, where the vegetation is mainly seasonally-dry forest mosaics interspersed with extensive areas of savannas (See Hoorn et al (2010)).…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 99%
See 3 more Smart Citations